2020
DOI: 10.20884/1.bioe.2020.2.3.3494
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was designated to reveal reproduction aspects of D. neapolitana that can support the domestication and cultivation of D. neapolitana. This research method is a survey method, and sampling was carried out three times at four points in the mangrove area of Jeruklegi Cilacap. The samples that have been taken are taken to the Animal Physiology Laboratory and stored in a bucket of 15 ppm brackish water and then aerated. The variables measured were the number of worm segments, worm body weight, the sex ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The oocytes' shape was rounded, and the diameter of the oocytes in the sexually submature worms ranged between 200 and 210 μm with an average of 205.8 μm, whereas sexually mature worms had oocytes with a diameter ranging between 220 and 230 μm with an average of 225.4 μm (Figure 1A.). These findings are in agreement with the study of Purwati et al (2020) in which Diopatra worms collected from Cilacap showed different levels of sexual maturity based on the diameter of the oocytes. The oocyte diameters of the sexually submature and mature female worms were below 200 μm and 208-240 μm, respectively, and the cells did not appear to have nurse cells.…”
Section: Sexual Maturitysupporting
confidence: 92%
See 4 more Smart Citations
“…The oocytes' shape was rounded, and the diameter of the oocytes in the sexually submature worms ranged between 200 and 210 μm with an average of 205.8 μm, whereas sexually mature worms had oocytes with a diameter ranging between 220 and 230 μm with an average of 225.4 μm (Figure 1A.). These findings are in agreement with the study of Purwati et al (2020) in which Diopatra worms collected from Cilacap showed different levels of sexual maturity based on the diameter of the oocytes. The oocyte diameters of the sexually submature and mature female worms were below 200 μm and 208-240 μm, respectively, and the cells did not appear to have nurse cells.…”
Section: Sexual Maturitysupporting
confidence: 92%
“…about 52% (Rachmad and Yuwono, 2000), and Jeruklegi, i.e. 60-66% (Wibowo et al, 2019) and 47-51% (Wibowo et al, 2020 a ). It was also lower than that of female epitokes of wawo worms (family Eunicidae) collected from Ambon, i.e.…”
Section: Macronutrient Contentsmentioning
confidence: 99%
See 3 more Smart Citations